Pengaruh Efikasi Diri dan Motivasi Berprestasi Terhadap Minat Melanjutkan Pendidikan ke Perguruan Tinggi Pada Peserta Didik SMK Negeri 44 Jakarta - Asiyah Khalisa Rokhimah; Roni Faslah; Maulana Amirul Adha (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study is to examine the influence of self-efficacy on students’ interest in continuing their studies to higher education, with achievement motivation as a mediating variable. The research employs a quantitative approach using the survey method. The population in this study consisted of 211 students from SMKN 44 Jakarta. The sampling technique used was proportionate stratified random sampling, calculated using the Slovin formula with a 5% margin of error, resulting in a total sample of 138 students. The data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4.0 software. The analysis process included the evaluation of the measurement model (outer model), the structural model (inner model), and hypothesis testing for direct and indirect effects. The results of the study demonstrate that: (1) self-efficacy has a positive and significant effect on achievement motivation; (2) self-efficacy has a positive and significant effect on students’ interest in continuing their studies to higher education; (3) achievement motivation also has a positive and significant effect on students’ interest in pursuing higher education; and (4) self-efficacy has a significant indirect effect on interest in continuing studies to higher education through achievement motivation as a mediating variable. These findings indicate that both self-efficacy and achievement motivation play important roles in shaping students' educational aspirations beyond secondary school. This study emphasizes the need for educational institutions to strengthen students’ belief in their own abilities and foster achievement motivation to increase their intention to pursue higher education. The findings contribute to the understanding of psychological factors that influence educational planning and can be used as a reference in developing academic guidance programs in vocational high schools.